Peningkatan Prestasi Belajar Siswa melalui Model Jigsaw dalam Pembelajaran PAI di SDN 76 Muaro Jambi - Andi Nurhasanah; Ibni Azka (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to improve student learning outcomes through the implementation of the cooperative learning model of the jigsaw type in science instruction for Grade V students at SDN 76/IX Muaro Jambi. This research is a Classroom Action Research (CAR) using the Kemmis & McTaggart model, which consists of four stages: planning, action, observation, and reflection. The research was conducted in two cycles to measure progressive improvements in student learning outcomes. Data collection techniques included observation, interviews, and documentation. The subjects were all 20 students of Grade V at SDN 76/IX Muaro Jambi. In the pre-cycle stage, before the intervention, only 25% of the students achieved satisfactory learning outcomes, which was categorized as